2000
DOI: 10.1093/hmg/9.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p160-mediated coactivation with increasing androgen receptor polyglutamine length

Abstract: Normal polymorphic size variation of the exon 1 CAG microsatellite of the androgen receptor (AR) is associated with prostate cancer, benign prostatic hyperplasia and male infertility. Furthermore, abnormal expansion of the satellite leads to Kennedy's disease. We have shown recently that the AR N-terminal domain (NTD), which contains the polyglutamine (polyQ) stretch (encoded by the CAG repeat), functionally interacts with the C-termini of p160 coactivators. In the present study we explored possible AR CAG siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(149 citation statements)
references
References 56 publications
5
142
1
1
Order By: Relevance
“…Normal CAG repeat number varies from 11 to 36 [9]. Previous studies in vitro have demonstrated that CAG repeat number shows an inverse correlation with AR activity [9][10][11][12][13][14]. Hence, it's not difficult to understand that shorter CAG repeats, increasing AR activity, are associated with prostate cancer [15,16], hirsutism [17] and hyperandrogenism in ovary [18,19], while longer CAG repeats, decreasing AR activity, are related to hypoandrogenicity [20] and male infertility due to impaired sperm production [10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Normal CAG repeat number varies from 11 to 36 [9]. Previous studies in vitro have demonstrated that CAG repeat number shows an inverse correlation with AR activity [9][10][11][12][13][14]. Hence, it's not difficult to understand that shorter CAG repeats, increasing AR activity, are associated with prostate cancer [15,16], hirsutism [17] and hyperandrogenism in ovary [18,19], while longer CAG repeats, decreasing AR activity, are related to hypoandrogenicity [20] and male infertility due to impaired sperm production [10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Across species, CAG repeat number has apparently increased along the lineage leading from basal primates to humans [29], which suggests that repeat length increases with lifespan across primates. Repeat length has been demonstrated to have a negative correlation with transactivation function [25,30], which is apparently due to a negative effect of repeat length on p160-mediated coactivation [31]. Recently, transgenic manipulations of CAG repeat length in a mouse model has experimentally demonstrated a negative correlation between repeat length and prostate cancer risk [32].…”
Section: Introductionmentioning
confidence: 99%
“…Upon androgen binding, AR undergoes conformational change, translocates into the nucleus, and recruits coactivator complexes for transactivation through direct DNA binding to androgen response elements (AREs) in AR target gene promoters (9,10). As observed in wild-type AR, polyQ-AR mutants reportedly translocate into the nucleus and recruit coactivator complexes to the AREs in a liganddependent manner (11).…”
Section: Spinal and Bulbar Muscular Atrophy (Sbma) Is A Neurodegeneramentioning
confidence: 99%